A Rickettsiella Endosymbiont Is a Potential Source of Essential B-Vitamins for the Poultry Red Mite, Dermanyssus gallinae - Price, Daniel R. G.; Bartley, Kathryn; Blake, Damer P.; Karp-Tatham, Eleanor; Nunn, Francesca; Burgess, Stewart T. G.; Nisbet, Alasdair J. (Frontiers in Microbiology, 2021)
Many obligate blood-sucking arthropods rely on symbiotic bacteria to provision essential B vitamins that are either missing or at sub-optimal levels in their nutritionally challenging blood diet. The poultry red mite Dermanyssus gallinae, an obligate blood-feeding ectoparasite, is a serious threat to the hen egg industry. Poultry red mite infestation has a major impact on hen health and welfare and causes a significant reduction in both egg quality and production. Thus far, the identity and biological role of nutrient provisioning bacterial mutualists from D. gallinae are little understood. Here, we demonstrate that an obligate intracellular bacterium of the Rickettsiella genus is detected in D. gallinae mites collected from 63 sites (from 15 countries) across Europe. In addition, we report the genome sequence of Rickettsiella from D. gallinae (Rickettsiella – D. gallinae endosymbiont; Rickettsiella DGE). Rickettsiella DGE has a circular 1.89 Mbp genome that encodes 1973 proteins. Phylogenetic analysis confirms the placement of Rickettsiella DGE within the Rickettsiella genus, related to a facultative endosymbiont from the pea aphid and Coxiella-like endosymbionts from blood feeding ticks. Analysis of the Rickettsiella DGE genome reveals that many protein-coding sequences are either pseudogenized or lost, but Rickettsiella DGE has retained several B vitamin biosynthesis pathways, suggesting the importance of these pathways in evolution of a nutritional symbiosis with D. gallinae. In silico metabolic pathway reconstruction revealed that Rickettsiella DGE is unable to synthesise protein amino acids and therefore amino acids are potentially provisioned by the host. In contrast Rickettsiella DGE retains biosynthetic pathways for B vitamins: thiamine (vitamin B1) via the salvage pathway; riboflavin (vitamin B2) and pyridoxine (vitamin B6) and the cofactors: flavin adenine dinucleotide (FAD) and coenzyme A (CoA) that likely provision these nutrients to the host.